1999
DOI: 10.1016/s0092-8674(00)81674-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of System N Suggests Novel Physiological Roles in Nitrogen Metabolism and Synaptic Transmission

Abstract: et al., 1983; Conti and Minelli, 1994). Since glia synthesize the glutamine used by neurons, this requires transfer of the amino acid between the two cell types (Ottersen et al., 1992). The role of glutamine in nitrogen metabolism and synaptic transmission thus involves

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
356
4
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 306 publications
(380 citation statements)
references
References 45 publications
19
356
4
1
Order By: Relevance
“…A fragment of the EST sequence AA190522 was amplified by PCR from fetal human brain cDNA and used to screen a rat brain cDNA library (Chaudhry et al, 1999). Sequence analysis indicated that one cDNA contained the entire open reading frame with an additional 140 bp 5Ј untranslated region (UTR) and an 820 bp 3Ј UTR.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A fragment of the EST sequence AA190522 was amplified by PCR from fetal human brain cDNA and used to screen a rat brain cDNA library (Chaudhry et al, 1999). Sequence analysis indicated that one cDNA contained the entire open reading frame with an additional 140 bp 5Ј untranslated region (UTR) and an 820 bp 3Ј UTR.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of pHi. Na ϩ /H ϩ exchanger-deficient PS120 cells were grown in DM EM with 5% fetal bovine serum, transfected with N-terminally hemagglutinin (HA)-tagged SA1, SA2, or SN1 cloned in the eukaryotic expression vector pcDNA3, and stable transformants selected in the neomycin analog G418 (Chaudhry et al, 1999). Colonies were picked after selection for 2-3 weeks and screened with commercially available antibodies to the HA epitope (Babco, Richmond, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, the glutamate released into the synaptic space by presynaptic neurons induces post-synaptic signaling through glutamate receptors, and is cleared by astrocytic excitatory amino acid transporters (EAAT1 and EAAT2, (Gegelashvili et al, 2007 andRothstein et al, 1994)), and then converted into glutamine through GS. The non-neuroactive glutamine is released into the extracellular space through astrocyte glutamine transporters (N and ASC-system transporter SN-1, SN-2 and ASCT2 (Chaudhry et al, 1999, Cubelos et al, 2005and Dolińska et al, 2004), and taken up by neurons (sodium-coupled amino acid transporter, SAT/ATA (Varoqui et al, 2000)), where it is converted back to glutamate via the action of PAG, in order to replenish the neurotransmitter pool. Therefore, astrocytic glutamate uptake prevents glutamate accumulation in the synaptic cleft and over-excitation of the postsynaptic neuronal receptors (Fig.…”
Section: Glutamine/glutamatementioning
confidence: 99%